Pengaruh Worklife Balance, Iklim Organisasi, dan Kompensasi Terhadap Kinerja Karyawan Struktural Akademik Universitas Al Ghifari Bandung - Fauzi Bukhori, Reza; Indriani, Yuanita; Mulyana, Iwan; Gunadi, Trida (Universitas Koperasi Indonesia, 2024)
This research aims to test and analyze the influence of Worklife Balance, Organizational Climate, and Compensation on Employee Performance (Case Study of Al Ghifari University Academic Structural Employees). The population in this study was 45 Structural Academic Employees at Al Ghifari University. The analysis used is multiple linear regression analysis to determine how much influence X1, X2, and X3 have on Y, both simultaneously and partially. The results of this research show that Worklife Balance, Organizational Climate, and Compensation have a significant positive effect on the Academic Structural Employee Performance of Al Ghifari University simultaneously or partially.